Longevity Risk in Korea - Yongok Choi (Korea Development Institute (KDI), 2016)
Korea's unprecedented rapid growth in life expectancy at birth is mainly attributable to a decline in elderly mortality rates. Indeed, the unanticipated increase in life expectancy and elderly population could complicate the government's long-term consolidation efforts and present a serious obstacle to formulating and streamlining policies. Accordingly, the next crucial step in the face of mounting longevity risk is to conduct preemptive research on Korea's elderly mortality rates. The government must acknowledge the exposure to longevity risk and make every efforts to compile accurate data on life expectancy and population projections in order to build a consensus on the gravity of the impending risks and seek a solution which could include a fiscal automatic stabilizer. - OECD statistics show that Korea's life expectancy has risen at the fastest pace among member nations. - It is highly likely that life expectancy estimates based on the period life table are underestimated compared to the actual average remaining life span. - Although unexpected longevity is prevalent across the globe, in terms of magnitude, Korea will experience a much bigger shock than any other developed country. - Despite reaching 80 years in 2008, Koreans' life expectancy continues to rise. - Analysis found that 80% of the increase in life expectancy after 2000 is attributed to the decrease in the mortality rates of those aged 50 years and over. - The elderly population has been consistently underforecast by Statistics Korea. - It has been found that the forecasting error for the 65 years and over population is approximately -10% on average in the previous population projections for for 15 years in the future. - Projections that take into account the recent improvement in mortality rates find that the 65 years and over population will reach 21.34 million by 2060, 21.1% more than Statistics Korea's estimates. - Accurate population projections are particularly important as huge social welfare expenditure with regards to aging is expected in the decades ahead. - Under-forecasting the elderly population could impose a serious obstacle to streamling existing policies by weakening the necessity to reform the social security system. - Recognition and mitigation efforts to tackle longevity risk should be of the utmost urgency. - Due to the consistently changing improvement patterns in Korea's mortality rates, Lee-Carter type models, which assume a universal pattern for mortality rate improvements, may not be suitable. - Longevity risk is an undiversifiable, systematic risk that cannot be shouldered by the government alone. The government should inform the public of the actual conditions of longevity risk, which would help to create an environment wherein economic agents can reach a consensus on burden-sharing.
Keywords: 330